(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Transformation of the world food market, caused by the change of China from the world's largest exporter into importer, and the expansion of the world food crisis, actualizes the need to solve the main problem of beekeeping – technical and technological backwardness. Automation and mechanization of beekeeping has a long history, however the high rates of the industry are achieved mainly due to the huge costs of manual labor, time and means. The amount of time, spent by beekeepers on the service of beehives, grows in direct proportion to the expansion of the apiary, and it can be seen as an obstacle to the development of the entire industry. Fitting of a beeswax foundation in the frame is one of the most labor-intensive technological operations [1]. Description of the device of the shallow frame (half-frame), which allows to abandon the traditional technology of fitting of a beeswax foundation in favor of the new – accelerated one, is presented. The device is a frame, divided longitudinally in two parts, connected together by loops. On the edges of the separated bars there are protrusions, which allow, while closing, to cut off the sheet of a beeswax foundation. The technical result of using the proposed device is simplification of the assembly process and reduction of labor costs while servicing beehive frames. The proposed device changes the traditional technology of fitting of a beeswax foundation, reducing the number of operations of the beekeeper to: opening the frame, positioning the standard sized sheet of a beeswax foundation in the frame, cutting the sheet to the required size while closing the frame. The usage of this device will allow the beekeeper to save a significant amount of time for performing other technological operations.